UPAYA KOREA SELATAN DALAM MELINDUNGI HAK CIPTA KOREAN WAVE DARI PEMBAJAKAN KONTEN DIGITAL - Ruth Yemima Exaudia Gintings (Journal of International Relations Universitas Diponegoro, 2023)
Korean Wave, also known as Hallyu, is a popular culture of South Korean entertainment industry such as music, movie, serial drama, webtoon, and etc. These contents are protected as part of intellectual property, especially copyrights. But, their popularities come with infringement action, where pirated sites show South Korean movies and drama without any permission from the copyright holder. This study aims to explain South Korea’s effort to protect these Korean Wave contents. The framework used in this research are the intellectual property concept, especially copyrights, the globalization concept, and the sovereignty concept (Westphalian System). The globalization concept tries to analyze its effort to protect Korean Wave. This study uses a qualitative research method with the type of descriptive research, data obtained through literature study. This research shows that South Korea pretty success in tackling copyrights issues, though they still can’t solve it thoroughly.